«ШӘРИЯР» ДӘСТАНЫНЫҢ МАЗМУНЫ ҲӘМ АТҚАРЫЛЫЎ ӨЗИНШЕЛИГИНИҢ ЖАНРЛЫҚ БЕЛГИЛЕР ЖАРАТЫЎҒА ҚАТНАСЫНЫҢ ГЕЙПАРА МӘСЕЛЕЛЕРИ - Кеңесбаева, Ш.К. (SCIENCE and SOCIETY, 2019)
The article deals with the genre peculiarities of the Karakalpak folklore epos «Shariyar», the other peoples don’t have the analogy to it. The author of the article compares different points of view on this issue in Karakalpak folklore and comes to the conlusion that this epos is not social-realistic, but it is a mythologic-fairy tale work.